Five Facets of Strategy: Unlocking Competitiveness in The Rolling Stock Industry - Atana, Arisal Maula; Pradana, Bayu Ilham (Jurnal Kewirausahaan dan Inovasi, 2025)
Purpose – This study aims to analyze the corporate strategy of PT Industri Kereta Api (Persero) (INKA) using the Diamond Strategy framework, which consists of five elements: arenas, vehicles, differentiators, staging, and economic logic. Design/Methodology/Approach – This study employs a qualitative descriptive approach using a case study method. Data were collected through in-depth interviews, documentation, and literature reviews to examine the implementation of INKA’s corporate strategy based on the Diamond Strategy framework. Findings – The results show that INKA’s corporate strategy incorporates all five elements of the Diamond Strategy, although their effectiveness varies. The elements of arenas and vehicles are implemented consistently, while staging and economic logic require further improvement, particularly in terms of internal integration and resource allocation. These findings emphasize the importance of strategic alignment among business elements to strengthen global competitiveness. Originality/Value This research provides value by applying the Diamond Strategy framework to a state-owned rolling stock manufacturer, offering new insights into how strategic elements interact and identifying areas requiring stronger internal integration to support more sustainable and globally competitive corporate strategies.